Facial Hemangioma Treated with Serial Intralesional Corticosteroid Injection: One Year Follow-up - Tjipta, Arya; Najatullah, Najatullah (Jurnal Plastik Rekonstruksi, 2012)
Background: Hemangioma is the most common tumors of childhood, affecting 5 to 10 percent of infants. They have a predilection for the head and neck region. Although having a somewhat predictable natural history evidenced by periods of proliferation, plateau, and involution; the timing of these distinct stages, the presence of complications, and the response to therapy are best characterized as unpredictable. Corticosteroids have been a component of the medical treatment for hemangiomas for over a half century. Intralesional injections purportedly localize the steroid effect to the given lesion and minimize unwanted systemic actions.Patient and Method : We report six patients with facial hemangioma, who required intralesional corticosteroid injection therapy. The number of corticosteroid injections given varied from 2-5 times at an interval of three weeks. The dosage given was 3-5 mg/kg/injection.Results : In our six cases, we found a significant decrease in bulkiness. And in three of our cases, patients were able to open their eyes on their own.Summary :The intralesional corticosteroid therapy was proven to be effective in our case-series.